2020
DOI: 10.3390/su12187345
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Coupled Heat Transfer Model Based on Groundwater Advection and Axial Heat Conduction for the Double U-Tube Vertical Borehole Heat Exchanger

Abstract: In this paper, a dynamic heat transfer model for the vertical double U-tube borehole heat exchanger (BHE) was developed to comprehensively address the coupled heat transfer between the in-tube fluid and the soil with groundwater advection. A new concept of the heat transfer effectiveness was also proposed to evaluate the BHE heat exchange performance together with the index of the heat transfer rate. The moving finite line heat source model was selected for heat transfer outside the borehole and the steady-sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…To reduce the capital cost of ground-source heat pipe systems, the authors expected that another heat transfer process by groundwater-advection heat flux could enhance the thermal performance of heat pipes in a typical site where groundwater flows actively toward the borehole. The advection effect has been validated in many theoretical studies [8,9] and reported in field studies [7,10]. However, few studies have demonstrated field evidence of enhancement of ground-source heat pipe systems with this method.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…To reduce the capital cost of ground-source heat pipe systems, the authors expected that another heat transfer process by groundwater-advection heat flux could enhance the thermal performance of heat pipes in a typical site where groundwater flows actively toward the borehole. The advection effect has been validated in many theoretical studies [8,9] and reported in field studies [7,10]. However, few studies have demonstrated field evidence of enhancement of ground-source heat pipe systems with this method.…”
Section: Introductionmentioning
confidence: 77%
“…The geothermal energy is extracted through the evaporation of the working fluid and transported upward to the condenser due to the temperature difference between the condenser and the evaporator [3]. At the condenser, the energy is dissipated to the heat sink (for example, snow on road surface which is then melted) and then the condensate returns to the evaporator by gravity to be heated again by the ground heat energy, consequently creating a cyclic process of evaporation and condensation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies investigated analytical models, which consider both conductive and advective heat transport in the subsurface for configuring BHEs [7,16,[24][25][26][27][28][29][30][31][32][33][34][35]. For instance, Claesson et al [27] introduced a groundwater g-function, which is used to reduce the values computed by a g-function for heat conduction.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a combination of the infinite cylinder source for short times and the finite MLS for larger times and a significant flow velocity is used. Zhang et al [35] combined the multipole method according to Hellström [37] with the finite MLS solution of Molina-Giraldo et al [32]. The models for the heat transfer inside (multipole method) and outside the borehole (finite MLS solution) are coupled by an iterative procedure [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation